Migration impact on left-behind women's labour participation and time-use: Evidence from Kyrgyzstan - Kamalbek Karymshakov; Burulcha Sulaimanova (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
This paper aims to study the impact of migration on labour supply and time-use of women left behind in Kyrgyzstan. Using the household survey data for 2011, labour supply is measured by occupational choices and working hours. Apart from the labour supply data, this study uses detailed information on daily time-use, which is analysed within women's occupations. This approach makes it possible to indicate the impact of migration not only through the labour supply analysis, which may be limited by reflecting labour market behaviour only, but also through the measure of allocation of time among different activities at home. To address the issue of endogeneity, the instrumental variable approach is applied. Results show that the migration of a household member increases the choice of left-behind women to be unpaid family workers. Most of the left-behind women choose unpaid family work and work more hours in this occupation. Although in the labour supply analysis wage-employment is not affected by migration, time-use model estimations reveal that wage-employed women are mostly affected through increases in the time for housework.
Keywords: E24; F22; J21; O53; 330; international migration; labour supply; women; Kyrgyzstan